Suboptimal aperture radar imaging by combination of pseudo‐polar formatting and gridless sparse recovery method. Issue 9 (8th April 2016) - Bao, Qian; Peng, Xueming; Lin, Yun; Zhang, Bingchen; Hong, Wen
Abstract : Imaging radar with a suboptimal aperture length usually has a poor azimuth resolution due to the limited aperture length and sparse non‐uniform linear array configuration. To address this problem, an imaging algorithm combining pseudo‐polar formatting and gridless sparse recovery method is proposed. After pseudo‐polar formatting the echo signal, reweighted atomic norm minimisation is implemented for azimuth imaging to achieve performance with improved resolution and free of off‐grid effect. Experiments on ground‐based synthetic aperture radar verify the performance of the proposed algorithm.